Public health and preventive medicine - Müllerová, Dana, 1962-; Bludovská, Monika; Kladnická, Iva; Langmajerová, Jana; Plavinová, Iveta; Sedláček, Pavel (Praha : Charles University - Karolinum Press, 2021)
It is a textbook for students of general medicine and dentistry, but it can also be used by health professionals or the professional non-medical public. Its goal is to provide information on preventive activities that can increase life expectancy and improve the quality of life of individuals and populations. The book provides an overview of the main topics of health protection and promotion and interactions between health and the environment with an emphasis on influenceable lifestyle factors in the prevention of chronic non-infectious diseases. ---------- Učebnicí pro studenty všeobecného lékařství a zubního lékařství, může však sloužit i zdravotníkům či odborné nelékařské veřejnosti. Jejím cílem je poskytnout informace o preventivních aktivitách, které mohou prodloužit délku života a zlepšit kvalitu života jednotlivců a populací. Kniha poskytuje přehled hlavních témat ochrany a podpory zdraví a interakcí mezi zdravím a životním prostředím s důrazem na ovlivnitelné faktory životního stylu v prevenci chronických neinfekčních onemocnění.
Bibliogr. odkazy
Keywords: zdravie verejné; lekárstvo preventívne; výživa; strava, stravovanie a diéty; učebnica